Optimization of 2D resistivity data image processing for modeling anomalous zones of disturbed phosphates - Bakkali, Saad (2005)
A Schlumberger resistivity record was made over an area of 50 hectares. A new field of processes based on the analytical signal response of the resistivity data was tested in the presence of disturbed phosphate deposits. Geology models were successively obtained from a peak model of the 2D resistivity data. The optimization of the imaging process was based on the optimization of surface tools. The descending analytical extension of the modeled surface over a depth of 30 meters was used for optimization of the modeling. The analytical processes found were consistently useful. The optimization of the phosphate reserve was improved and better constructed.